1997
DOI: 10.1023/a:1005747711084
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow micrometastases in 109 breast cancer patients: Correlations with clinical and pathological features and prognosis

Abstract: In our series, bone marrow positivity did not correlate with prognostic parameters or prognosis. Of interest is the relative excess of positivity when the bone marrow was obtained during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 17 publications
1
21
0
3
Order By: Relevance
“…These results are consistent with two previous studies (16,17), but in contrast to the work of Ikeda et al (13), who found that positivity of axillary lymph node metastases and lymphatic vessel invasion were significantly higher (P Ͻ 0.05) in the CK19 PCR-positive patients than the negative patients.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with two previous studies (16,17), but in contrast to the work of Ikeda et al (13), who found that positivity of axillary lymph node metastases and lymphatic vessel invasion were significantly higher (P Ͻ 0.05) in the CK19 PCR-positive patients than the negative patients.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, the antibodies used in their study have not been tested in other clinical trials, and the specificity of these can be questioned. Furthermore, their BM analyses at diagnosis did not correlate to clinical outcome (24). In other studies, repeated BM examinations have mostly been performed in high-risk and metastatic breast cancer patients receiving high dose chemotherapy and/or immunotherapy (10,25,26).…”
Section: Discussionmentioning
confidence: 97%
“…The search for epithelial cells by immunocytochemical (IC) techniques in the bone marrow (BM) has been already studied by several authors as a potential prognostic factor for patients [2][3][4] with breast cancer (BC) and more recently as a potential marker of response to adjuvant chemotherapy [5]. In fact, a previous meta-analysis has been conducted in 1998 by Funke and Schraut [6] in order to summarize the evidence regarding the prognostic utility of this methodology.…”
Section: Introductionmentioning
confidence: 99%